2001
DOI: 10.1007/s004640000358
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intraoperative complications on adhesion formation during laparoscopic and conventional cholecystectomy in an animal model

Abstract: It seems that LC has a lower rate of adhesion formation than the conventional open technique. Complications such as bleeding or laceration of the liver bed during LC can enhance adhesion formation. No adhesion formation can be mentioned in relation to gallbladder perforation during LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
(18 reference statements)
0
15
0
3
Order By: Relevance
“…Every abdominal operation can induce adhesion formation, although in general it has been shown that laparotomy results in more adhesion formation than laparoscopy [18-21]. Another cause for the formation of adhesions is the presence of localized or generalized peritonitis [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Every abdominal operation can induce adhesion formation, although in general it has been shown that laparotomy results in more adhesion formation than laparoscopy [18-21]. Another cause for the formation of adhesions is the presence of localized or generalized peritonitis [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…We showed that with LC, only a decreased degree of columnar adhesions developed, whereas dense and curtain-like adhesions were formed with OC [4].…”
Section: Resultsmentioning
confidence: 93%
“…Thus, the laparoscopic approach, when viable, can be considered to prevent obstruction due to adhesions (Tittel et al, 2001). Other clinical and experimental studies have also shown evidence of a lesser formation of adhesions at the surgical site and on the abdominal wall when laparoscopy is used (Gadallah et al, 2001;Gamal et al, 2001). The lysis of adhesions by the laparoscopic route has several theoretical advantages over open surgery: 1) less intense postoperative pain, 2) more rapid resolution of the ileum, 3) shorter hospitalization, 4) earlier return to daily activities, 5) lower incidence of complications of the surgical wound, and 6) a reduced formation of postoperative adhesions (Nagle et al, 2004).…”
Section: Laparoscopy In Abdominal Sepsis Due To Affections Of the Smamentioning
confidence: 95%